Middle-Preserving Pancreatectomy for Multifocal Metastatic Renal Cell Carcinoma Located in the Head, Body and Tail of the Pancreas. A Case Report - Ohzato, Hiroki; Yamamoto, Tameyoshi; Fukunaga, Mutsumi; Imamura, Hiroshi; Furukawa, Hiroshi (JOP. Journal of the Pancreas, 2010)
Context Postoperative endocrine and exocrine insufficiencies following traditional pancreatectomies might cause a deterioration of the quality of life and surgical outcome. Parenchyma-sparing pancreatectomies have been utilized in benign lesions and low-grade malignancies. Case report A 67-year-old female with a past history of right nephrectomy for renal cell carcinoma 20 years earlier was referred to our institute with obstructive jaundice and multiple nodules in the pancreas. Computed tomography demonstrated five well-demarcated, strongly enhanced nodules with diameters of 5.5 cm in the head, 2.0 and 1.8 cm in the body, and 1.2 and 1.0 cm in the tail. Fluorine-18 fluorodeoxyglucose positron emission tomography did not demonstrate any extrapancreatic uptake. A middle-preserving pancreatectomy was performed after ultrasonography had confirmed arterial perfusion in the middle segment. A histological study demonstrated metastatic clear cell renal carcinoma. To date, the patient has remained without recurrence for two and a half years since surgery. A minimal administration of insulin has been necessary; however, C-peptide is detectable and nutritional status is comparatively good. Conclusion A middle-preserving pancreatectomy is a useful procedure in a parenchyma-sparing pancreatectomy for resecting multifocal lesions in the head, body and tail of the pancreas. Image: Procedure for a middle-preserving pancreatectomy: reconstruction following a middle-preserving pancreatectomy.